Patient participation in decision-making about cardiovascular preventive drugs - resistance as agency - Josabeth Hultberg; Carl Edvard Rudebeck (Taylor & Francis Group, 2017)
Objective: The aim of the study was to describe and explore patient agency through resistance in decision-making about cardiovascular preventive drugs in primary care. Design: Six general practitioners from the southeast of Sweden audiorecorded 80 consultations. From these, 28 consultations with proposals from GPs for cardiovascular preventive drug treatments were chosen for theme-oriented discourse analysis. Results: The study shows how patients participate in decision-making about cardiovascular preventive drug treatments through resistance in response to treatment proposals. Passive modes of resistance were withheld responses and minimal unmarked acknowledgements. Active modes were to ask questions, contest the address of an inclusive we, present an identity as a non-drugtaker, disclose non-adherence to drug treatments, and to present counterproposals. The active forms were also found in anticipation to treatment proposals from the GPs. Patients and GPs sometimes displayed mutual renouncement of responsibility for decision-making. The decision-making process appeared to expand both beyond a particular phase in the consultations and beyond the single consultation. Conclusions: The recognition of active and passive resistance from patients as one way of exerting agency may prove valuable when working for patient participation in clinical practice, education and research about patient-doctor communication about cardiovascular preventive medication. We propose particular attentiveness to patient agency through anticipatory resistance, patients' disclosures of non-adherence and presentations of themselves as non-drugtakers. The expansion of the decision-making process beyond single encounters points to the importance of continuity of care.KEY POINTS Guidelines recommend shared decision-making about cardiovascular preventive treatment. We need an understanding of how this is accomplished in actual consultations.This paper describes how patient agency in decision-making is displayed through different forms of resistance to treatment proposals. •The decision-making process expands beyond particular phases in consultations and beyond single encounters, implying the importance of continuity of care. •Attentiveness to patient participation through resistance in treatment negotiations is warranted in clinical practice, research and education about prescribing communication.